Testing the Therapeutic Equivalence of Alogliptin, Linagliptin, Saxagliptin, Sitagliptin or Vildagliptin as Monotherapy or in Combination with Metformin in Patients with Type 2 Diabetes - Messori, Andrea (Springer Healthcare, 2014)
BACKGROUND: In studying the therapeutic evidence of innovative drug treatments, increasing attention is being devoted to differentiating between results that indicate no significant differences among the treatments under examination (“no proof of difference”) and results that demonstrate the therapeutic equivalence among the treatments (“proof of no difference”). AIM: Our analysis was aimed at evaluating the degree of therapeutic equivalence for dipeptidylpeptidase-4 (DPP-4) inhibitors given in type 2 diabetes as monotherapy or in combination with metformin. METHODS: Equivalence was determined by developing a standard Forest plot that incorporated the information on margins previously reported in randomized trials on these agents. The end point was HbA(1c) change from baseline; the equivalence margin was set at ±0.25% change in HbA(1c). The clinical material was obtained from a systematic review on this topic. RESULTS: Given as monotherapy, linagliptin, sitagliptin, and vildagliptin (but not saxagliptin) met the equivalence criterion when compared with one another. Given in combination with metformin, linagliptin, saxagliptin, sitagliptin, and vildagliptin showed an equivalent effect whereas alogliptin did not satisfy the equivalence criterion. CONCLUSIONS: Considering the most recent therapeutic guidelines, our results are of interest particularly as regards the information on DPP-4 inhibitors in combination with metformin. Four of the five DPP-4 inhibitors under examination clearly showed to have the same effectiveness; the fifth agent—alogliptin—failed to meet the equivalence criterion, but only because its superiority could not be excluded. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s13300-014-0066-y) contains supplementary material, which is available to authorized users.